Potential of Tax Avoidance Based on Fraud Hexagon in Manufacturing Companies in BEI in Tax Avoidance Practice - Wahyuni, Dwi Sri; Pramiana, Omi (Pertapsi-Indonesia collaborated with Petra Christian University, 2024)
This research aims to determine the influence of pressure, opportunity, rationalization, competence, arrogance and collusion on tax avoidance in manufacturing companies on the IDX in carrying out tax avoidance practices in 2021-2022. This research uses a quantitative descriptive method, with a total of 27 companies as a sample with 54 data used obtained through company annual reports. The results of this study show that the pressure variable proxied by ROA has an effect on tax avoidance, the opportunity variable proxied by the proportion of independent board of commissioners (BDOUT) has no effect on tax avoidance, the rationalization variable proxied by audit opinion has an effect on tax avoidance, the competency variable which is proxied with changes in directors having no effect on tax avoidance, the arrogance variable which is proxied by CEO narcissism has no effect on tax avoidance, the collusion variable which is proxied by political connections has an effect on tax avoidance.